Test on full-scale three-storey steel moment frame and assessment of ability of numerical simulation to trace cyclic inelastic behaviour. - Nakashima, Masayoshi (Earthquake engineering & structural dynamics.)
A test on a full-scale model of a three-storey steel moment frame was conducted, with the objectives of acquiring real information about the damage and serious strength deterioration of a steel moment frame under cyclic loading, studying the interaction between the structural frame and non-structural elements, and examining the capacity of numerical analyses commonly used in seismic design to trace the real cyclic behaviour. The outline of the test structure and test program is presented, results on the overall behaviour are given, and correlation between the experimental results and the results of pre-test and post-test numerical analyses is discussed. Pushover analyses conducted prior to the test predicted the elastic stiffness and yield strength very reasonably. With proper adjustment of strain hardening after yielding and composite action, numerical analyses were able to accurately duplicate the cyclic behaviour of the test structure up to a drift angle of 1/25. The analyses could not trace the cyclic behaviour involving larger drifts in which serious strength deterioration occurred due to fracture of beams and anchor bolts and progress of column local buckling.